In search of deep faith : a pilgrimage into the beauty, goodness, and heart of Christianity - Belcher, Jim, 1965- (Downers Grove, Illinois : InterVarsity Press, an imprint of InterVarsity Press, 2013)
"Grappling with [questions about faith and meaning], Jim Belcher set out on a quest to see how the Christian faith faces the challenges of the modern world and answers the cries of the human soul. Seeking renewal after a draining season of life, he and his family spent a year traveling through Europe, exploring the faith that has shaped civilizations throughout the centuries"--Amazon.com.
Includes bibliographical references (pages 297-315) and index.
Keywords: Christian pilgrims and pilgrimages -- Europe; Christian pilgrims and pilgrimages -- England -- Oxford; Voyages and travels -- Religious aspects -- Christianity; Christian pilgrims and pilgrimages; Voyages and travels -- Religious aspects -- Christianity; England -- Oxford; Europe